Legal Pluralism and Responsive Legal Development: The Role of Pageu Gampong in Strengthening Sharia Implementation in Aceh - Azwarfajri, Azwarfajri; Muliadi Nur; Yusuf, Muhammad; Hakim, Lukman (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
The implementation of Islamic law (Sharia) in Aceh has led to a dual legal system, but its effectiveness is often challenged by a disconnect between the formal legal framework and the community's legal culture. This article argues that a purely legal-positivist approach, which relies heavily on state-enforced qanuns, is insufficient. A more effective strategy requires a responsive legal development model that integrates Sharia with deeply rooted local wisdom. This study, utilizing a descriptive-qualitative approach based on a literature review, examines the potential of the pageu gampong system—a traditional village-level institution for social and moral harmony—as a strategic solution. Our analysis shows that revitalizing pageu gampong can bridge the gap between formal law and community practice by functioning as both a preventive and repressive mechanism. By fostering community participation and leveraging the legitimacy of customary leaders, this system not only addresses the challenges of enforcement but also strengthens public trust and combats the rise of individualism, thereby making Sharia implementation more sustainable and effective